KERJA ARTIKULATIF PEREMPUAN PESANTREN DI SUMENEP MADURA DALAM MENJAGA BUMI - zaitur rahem; Ahsan Irodat; Kosasih Kosasih; Nurkhairina Nurkhairina (Staisman Press, 2025)
Islamic boarding schools are the locomotive in driving environmental rescue actions. Groups of students from several levels of educational units at this Islamic boarding school, through mentoring from educators (Teachers, Lora, Neng, Nyai, and Kiai), take direct action, competing to save the environment from the onslaught of plastic waste. This movement symbolically marks the total involvement of Islamic boarding school circles in saving the earth from an unfriendly climate. Students who are members of the Waste Scavenger group are specifically involved in socializing the dangers of plastic waste or non-organic waste and environmental issues in general. One of the benefits of this Waste Scavenger Movement among students is to educate people's mindsets and lifestyles about waste and their environment. The santri movement as an anticipation in reducing (reduce, or reusing (reuse) and/or recycling (recycle). At the local level, namely in the Islamic boarding school environment, this group of santri strives to become pioneers in society to be more concerned with waste, cleanliness, environmental sustainability and healthy living. This Garbage Scavenger has three teams. Namely, the plastic waste team, the organic fertilizer team and the local food team. The santri movement to care about the environment through recycling waste substantially strengthens the identity of santri as mundziru al qaum, people who have scientific disciplines and use them for the benefit of life around them. The santri mobilize and ground the understanding of the yellow book text whose breath is environmental fiqh or ecological fiqh.